2020
DOI: 10.1177/1073274820934805
|View full text |Cite
|
Sign up to set email alerts
|

Power and Promise of Next-Generation Sequencing in Liquid Biopsies and Cancer Control

Abstract: Traditional methods of cancer treatment are usually based on the morphological and histological diagnosis of tumors, and they are not optimized according to the specific situation. Precision medicine adjusts the existing treatment regimen based on the patient’s genomic information to make it most suitable for patients. Detection of genetic mutations in tumors is the basis of precise cancer medicine. Through the analysis of genetic mutations in patients with cancer, we can tailor the treatment plan for each pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 144 publications
(181 reference statements)
1
13
0
Order By: Relevance
“…However, many existing liquid biopsies with a focus on early cancer detection lack the sensitivity required for reliable detection of early stage cancers [ 11 ]. For example, tumor derived genetic biomarkers are not always shed into the blood stream in early stages, and even when they are shed in to the bloodstream, they exist at very low concentrations [ 12 , 13 ]. Cancer protein biomarkers such as prostate specific antigen (PSA) and carcinoma antigen-125 (CA-125) are often not elevated in cancer patients, even in those with advanced cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many existing liquid biopsies with a focus on early cancer detection lack the sensitivity required for reliable detection of early stage cancers [ 11 ]. For example, tumor derived genetic biomarkers are not always shed into the blood stream in early stages, and even when they are shed in to the bloodstream, they exist at very low concentrations [ 12 , 13 ]. Cancer protein biomarkers such as prostate specific antigen (PSA) and carcinoma antigen-125 (CA-125) are often not elevated in cancer patients, even in those with advanced cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four of the mutant versions like SLC3A2, KIAA0368, CADPS2, and CTSB were targeted using tumor infiltrated lymphocytes [39]. Thus, this study served as an example that the genomic information of tumors detected by NGS can be used to identify patients who may respond to immunotherapy methods to induce the body's immune system to attack and treat tumors [40].…”
Section: Clinical Applications Of Ngsmentioning
confidence: 99%
“…These variations in the mutation can be identified with the help of NGS, thus making it easier to classify the cancer subtype [41]. NGS has boosted the discovery of unknown genes that may be linked to improved treatment response and the development of drug resistance [40].…”
Section: Clinical Applications Of Ngsmentioning
confidence: 99%
“…Blood-based liquid biopsy, as an alternative to tumor biopsy, might improve the management of patients with mBC, as numerous studies have demonstrated its usefulness for cancer prognosis, diagnosis, and interestingly for the prediction of response or resistance to administered therapeutics [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%